Samarium Diiodide Catalyzed Radical Cascade Cyclizations that Construct Quaternary Stereocenters - Huang, Huan-Ming; He, Qiong; Procter, David J. (Synlett, 2020)
SmI2-catalyzed radical cascade cyclizations were used to generate complex carbocyclic products bearing quaternary stereocenters with high selectivity. Bicyclic scaffolds containing four contiguous stereocenters and one quaternary stereocenter were obtained in excellent yields (up to 99%) and with high diastereocontrol by using 5 mol% of SmI2 at ambient temperature in the absence of co-reductants or additives. Mechanistic studies support a radical relay mechanism.
Keywords: radical relay; catalysis; samarium diiodide; cascade reaction; cyclization